Smart Environmental Governance: Digital Transformation of the Riau Hijau Policy in Indonesia - Safitri, Kinanti Indah (Universitas Muhammadiyah Yogyakarta, 2025)
The Riau Hijau Policy is a strategic initiative of the Riau Provincial Government to balance economic growth with environmental sustainability through three pillars: environmental degradation control, improved natural resource governance, and increased utilization of renewable energy. However, the integration of digital technologies into policy execution remains underexplored in academic and policy discourse. Addressing this gap, this study aims to analyze how digital transformation can enhance Riau Hijau while identifying the key challenges that hinder its effectiveness. The research adopted a descriptive qualitative approach combining document analysis of regulations and reports with in-depth interviews involving government officials, academics, NGOs, and community representatives. The findings revealed that digital tools have significant potential to strengthen real-time environmental monitoring, data-driven decision making, and public participation. Nevertheless, several obstacles persist, including regulatory gaps, uneven digital infrastructure, limited human resource capacity, and insufficient funding for green innovations. This study contributes a comprehensive model of Smart Environmental Governance that links technological transformation with sustainable policy execution. It provides local insights from Riau Province while situating these findings within global debates on green policy and sustainable development. The strategies for regulatory reform and inclusive digital infrastructure are adaptable to similar environmental challenges in other developing economies.